Problematika Mutu Pendidikan Islam Dalam Pencapaian Kompetensi Lulusan di Perguruan Tinggi Agama Islam Negeri - Novita Dwi Astuti; Laily Farihatul Izza (Fakultas Agama Islam Universitas Al Washliyah, 2025)
Quality in the field of education is a depiction of the characteristics or standards of the educational process that has been established. This is determined through careful planning and processes to produce graduates who are competent according to the chosen educational focus. The research method used is a descriptive qualitative approach, which will explain the findings from the researcher. The results found by the researcher include the competency of graduates from Islamic higher education institutions being less competent, as well as strategies or efforts that can be undertaken by universities to improve the quality of education at these higher education institutions. It can also lead to improvements, innovations, and oversight from the higher education institutions.